Estimation of Groundwater Recharge i n Oil Producing Areas of the N iger Delta Basin of Nigeria: Usi ng Soil Moi sture Deficit Techniq ue - Luke, Obiejesi (Biological Sciences - PJSIR, 2007)
. The st udy was u nd er taken t o pr ed i ct n atu ra l and i n c iden t a l ground w ater r ech a rge u si n g th e Ill i st u r e de fi c i tcch n i q u t: . I t eval u a t 1.:s t h e rat e of co 11t t1 111i n u nts i nflow i nto th e ph reat i c aq u i fer s of t h e N i ger Del t a Basi n . Th e computer 111od e l u sed basi c h yd rol ogi ca l and agro-111etcorol ogicu l i n put param et er · u ch as ra i n fa l l , poten t i a l evapo-tran sp i ru t i on , ru n off coe rri ci ent, we i gh t ed r o t con stan t u n d oi I and gas c:x I l ora t i on/ prod u ct i on sp i 11 dat n of 3 yea rs t o e ·t i111a te t h e i n ci dents of rech a rge on d a i l y ba ses. Th e mod e l wa s app l i ed to sel ected ft1u r n on -over l a pp i n g pot en t i a l sp i l l si t es w i t h i n t h e on sh ore a n:u bu sed on a vu i l a b l data an d geol ogy/ soi l t y pes. Th e st ud y i nd i ated th a t t h e da i l y n a t u rnl rech a rge ra n ged from zcrn t o 1 20 111111 . Avera ge m ont h l y ,md an n ua l natu ra l rech u rgc va ri ed from zero to 585111111, a nd rro111 1 41 6 t o 2044 111111 , r e peL:l i ve l y. Th e st ud y estab l i ·h ed rech a rge coeff i c i en t s or 0. 1 43 t u 0.365 for th e an:a , wi t h 95% con fid en ce l i m i t. l ( x te n si w te st s tktcrm i n ed th at t h e mod el resu l t s are the m ost sen si t i ve to var i at i on s i n ra i n fa l l , eva po rat i on an d sp i l l Jat a . The esti m a ted rech arge coeffi ci ents we r e i n agreem ent w i t h th e ea rl i er r eported ra n ge of 0.08 t o 0.30.